2018
DOI: 10.1016/j.trci.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The hidden variables problem in Alzheimer's disease clinical trial design

Abstract: As the leading cause of dementia worldwide, Alzheimer's disease has garnered intense academic and clinical interest. Yet, trials in search of a disease-modifying therapy have failed overwhelmingly. We suggest that, in part, this may be attributable to the influence of disruptive variables inherent to the framework of a clinical trial. Specifically, we observe that everyday factors such as diet, education, mental exertion, leisure participation, multilingualism, sleep, trauma, and physical activity, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Seventh, we did not include a physically active control condition such as a combined aerobic, balance, and strength training program. Eighth, we did not control for the effect of concurrent medication use including for example cholinesterase inhibitors, memantine, typical and atypical antipsychotics, antidepressants, and benzodiazepines, although it is known they may act as potential confounders and disruptors in MNCD trials [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seventh, we did not include a physically active control condition such as a combined aerobic, balance, and strength training program. Eighth, we did not control for the effect of concurrent medication use including for example cholinesterase inhibitors, memantine, typical and atypical antipsychotics, antidepressants, and benzodiazepines, although it is known they may act as potential confounders and disruptors in MNCD trials [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical trials for AD have failed [ 33 ], and this may, in part, be attributable to heterogeneous pathology and varying lifestyle and medical factors (e.g. diet, education, mental exertion, leisure participation, multilingualism, sleep, trauma, physical activity, concurrent medications and illnesses) [ 34 ]. It has been suggested that future clinical evaluation of AD therapeutics should consider the potential impact of these variables [ 34 ], and brain age may act as a holistic measure of multiple processes that converge on neurodegeneration in various ways.…”
Section: Discussionmentioning
confidence: 99%
“…In the longitudinal study by Maheswaran et al which included transgenic and WT mice, it was found that the WT mouse brain enlarged from 6 to 14 mo, including the whole brain volume, ventricles, and white matter, whereas grey-matter rich regions declined [31]. Of note, studies of aging in mice is well justified because of the access to tissues, the potential for transgenic comparisons, and the lower cost, compared to human studies that require huge study inclusion numbers and an entire lifespan to rule out confounding factors [44]. The objective of this study was to determine features of vascular brain aging in middle-aged and old C57BL/6J mice, a common WT strain used for brain research studies, and to compare and optimize MRI methods with results indicative of brain age.…”
Section: Structural Features Of Brain Agingmentioning
confidence: 99%